2021
DOI: 10.21037/atm-21-621
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-mediated improvement of renal mitochondrial function via the AMPK/PGC-1α/NRF-2 pathway is superior to norepinephrine in a rat model of septic shock associated with acute renal injury

Abstract: Background: This study sought to compare the therapeutic effects of angiotensin II (ANG II) and norepinephrine (NE) on cecal ligation and puncture (CLP)-induced septic acute kidney injury (AKI) in rats.Methods: Sepsis shock was induced in anesthesia Sprague-Dawley male rats by CLP model for 24 hours.A total of 40 rats were divided into five groups, including control group, sham group, CLP group, CLP + ANG II group, and CLP + NE group. CLP + ANG II and CLP + NE group were administration of ANG II or NE after se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…Our results showed that neither meldonium nor treatments significantly altered PGC1-α protein level in any of the examined tissues ( Figure 5 ), in contrast to studies on different models of sepsis showing a reduction of PGC1-α content in the heart, kidney, and liver [ 76 , 77 , 78 , 79 ]. Since the proposed mechanism of PGC1-α downregulation under the septic conditions includes NF-kB activation [ 80 , 81 ], which we did observe, the supposed inconsistency between our results and those previously published could be explained by the difference in the experimental designs.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that neither meldonium nor treatments significantly altered PGC1-α protein level in any of the examined tissues ( Figure 5 ), in contrast to studies on different models of sepsis showing a reduction of PGC1-α content in the heart, kidney, and liver [ 76 , 77 , 78 , 79 ]. Since the proposed mechanism of PGC1-α downregulation under the septic conditions includes NF-kB activation [ 80 , 81 ], which we did observe, the supposed inconsistency between our results and those previously published could be explained by the difference in the experimental designs.…”
Section: Resultscontrasting
confidence: 91%
“…Since the proposed mechanism of PGC1-α downregulation under the septic conditions includes NF-kB activation [ 80 , 81 ], which we did observe, the supposed inconsistency between our results and those previously published could be explained by the difference in the experimental designs. Specifically, the experimental design mentioned in the literature implied tissue collection 12–72 h following the sepsis induction [ 76 , 77 , 78 , 79 ]. In contrast, we collected organs as early as within 8–9 h due to the high mortality rate following FIP injection.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK, an upstream enzyme of Nrf2, enhances the expression of antioxidant genes, thereby inhibiting oxidative damage. 79 Additionally, AMPK can trigger the phosphorylation of residue Ser558 (Ser550 in mice) on Nrf2, influencing the nuclear accumulation of Nrf2. 80 Notably, following the mutation of this residue, the activation of AMPK is unable to promote the nuclear import of Nrf2.…”
Section: Ampk/nrf2 Signaling Pathwaymentioning
confidence: 99%